Performance Analysis of Direct Torque Control method for Traction System based on IPMSM - Han, Byeol; Lee, June Seok; Bak, Yeongsu; Lee, Kyo Beum (Journal of the Korean Society for Railway, 2020)
This paper presents performance analysis of a direct torque control (DTC) method for a traction system based on an interior permanent magnet synchronous motor (IPMSM). The IPMSM of the traction system has to be effectively controlled from constant torque region to constant power region because it must operate over the entire speed range and under all environmental conditions. Algorithms for the traction system can be divided into two categories: one is field oriented control (FOC), the other is DTC. In FOC, the currents of the d-q axis are controlled for maximum torque per ampere (MTPA) control in the constant torque region and for field weakening (FW) control in the constant power region. Different from FOC, DTC involves direct control of stator flux and torque, and so this method requires the calculation of reference stator flux and torque for MTPA and FW control. In this paper, performance analysis of IPMSM and power loss analysis of a power semiconductor between FOC and three different DTC algorithms over the entire speed range are presented. The effectiveness of the methods discussed in this paper is verified by simulation results.
Keywords: : IPMSM; Direct torque control; Field oriented control; Field weakening control; Maximum torque per ampere